THE INFLUENCE OF COOPERATIVE INTEGRATED READING ANDCOMPOSITION (CIRC) MODEL ON ELEMENTARY STUDENTS’ LITERACY - Tatat Hartati; Anggi Citra Apriliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe comprehensively the effect of Cooperative Integrated Reading and Composition (CIRC) model on the literacy abilities of elementary school students. The results of this study were expected to provide information about innovative models to be implemented in order to improve the literacy skills of elementary school students. This study utilized pre-experimental research method referring to research conducted on one experimental group whose sample was not randomly selected and there was no control group. This method was used to determine the effect of CIRC model on students' literacy skills after being given a treatment. The design in this study was one group pretest-posttest design. There was a significant effect of using Cooperative Integrated Reading and Composition (CIRC) model on the literacy abilities of fourth grade elementary school students. The average of overall pretest scores was 65.3. Then, it was obtained that the average posttest scores after the treatment was 86.1. Thus, there was a significant effect of CIRC model on the literacy abilities of elementary school students. as a result, the CIRC learning model could be implemented asan alternatives to increase the literacy skills in elementary school students.